Analysis of Pixel Values in Lateral Os Sacrum Radiographic Examinations Using Various Virtual Grid Ratios - Yustiyo, Rafhael Reznandika; Sutoro, Shinta Gunawati; Irsal, Muhammad; Rizqi, Muhammad; Ardoni, Fitrus (Poltekkes Kemenkes Riau, 2025)
Lumbosacral lateral projection radiography, particularly of the fifth lumbar vertebra (L5) and Sacrum, often experiences a decrease in contrast due to exposure factors and object thickness. This study aims to analyze the variation in the Virtual Grid ratio of 8:1, 10:1, and 12:1 in lateral projection sacrum examinations using the Pixel Value indicator. This descriptive quantitative study was conducted in May–June 2025 at the Radiography and Physics Laboratory, Department of Radiodiagnostic and Radiotherapy Technology, Jakarta II Polytechnic. The sample consisted of lateral sacrum images with three grid ratio variations. Analysis was performed on the average Pixel Value, followed by statistical testing using SPSS 27 with the One-Way ANOVA method. The results showed the average Pixel Value: 8:1 ratio at 150.94; 10:1 ratio at 150.46; and 12:1 ratio at 152.75 with P>0.05, indicating no significant difference between the grid ratio variations.